The Correlation of Aerobic and Anaerobic Capacities with Performance in Badminton Matches - Tommy Apriantono; Indria Herman; Nia Sri Ramania; Rini Syafriani; Bagus Winata; Sri Indah Ihsani; Agung Dwi Juniarsyah; Muhamad Fahmi Hasan (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
The purpose of this study was to measure the aerobic and anaerobic capacities of badminton athletes, and to relate them to performances, such as the number of drive shots, lob shots, or smash shots, in badminton matches. 12 badminton athletes in the men's doubles category carried out two types of measurements, namely laboratory test and match test. Laboratory tests included the VO2max test using the Lode Quark Cardio Pulmonary Exercises Test (CPET), as well as a battery test (push-up, back-up, sit-up, and half-squat). Match test was conducted using competition match system. Match performances, such as drive shots, lob shots, or smash shots were analyzed by experts. The higher the VO2max level of the pair of men's doubles athletes, the better its correlation with their badminton strokes was. For example, pair 1 (native 1 and native 2) had a mean VO2max of 54.2 ± 0.9 ml/kg/min and performed the average numbers of lob strokes of 35.5 ± 0.7, drive shots of 47.5 ± 0.7, and smash of 19.5 ± 7.8. The lowest result was found in pair 6, in which the VO2max level was 47.6 ± 0.4. The average numbers of shots performed by this pair were 23.5 ± 2.1 for lob, 29.5 ± 0.7 for drive, and 5.5 ± 0.7 for smash. On the other hand, Pair 1 had the highest average repetition of the battery test compared to the other pairs (Push-up = 35.5 ± 0.7, Back-up = 49.5 ± 0.7, Sit-up = 55.0 ± 0.0, Half-squat = 69.5 ± 0.7), and it was directly proportional to the results of hitting performance in a match. This study shows that there is a correlation between VO2max average and battery test results and the performance of badminton men's doubles athletes.